Therapeutic potential of Ceratonia siliqua extract for the management of asthma and hypertension - Hamid, Irfan; Janbaz, Khalid Hussain; Iqbal, Rabia; Akhtar, Muhammad Furqan; Saleem, Ammara; Ali, Sajid; Sharif, Ali; Akhtar, Bushra; Javaid, Zeeshan; Sohail, Kashif (Cellular and Molecular Biology, 2022)
The current work was performed to explore the pharmacological mechanisms involved in the management of asthma and hypertension along with the safety profile of the Ceratonia siliqua (C. siliqua/Carob) pods. The bronchorelaxant, vasorelaxant, and cardioselective activities of C. siliqua pods were investigated using isolated rabbit tracheal, aortic, and paired atrial fragments on the Power lab data acquisition system. Normotensive rats were used to study antihypertensive activity. The plant extract and its fractions relaxed the carbachol-induced contraction in the tracheal fragments and shifted the concentration-response curve of carbachol towards the right confirming the muscarinic receptor antagonist activity. The relaxation of phenylephrine-induced contraction in an aortic fragment by the extract showed α- adrenergic blocking activity. Furthermore, the extract produced a cardio-selective response in the paired atria and decreased the blood pressure in anesthetized normotensive rats. The plant extract proved to be non-toxic in oral acute and chronic toxicity studies and did not demonstrate any sign of histopathological lesions. These results suggested that the plant extract was non-toxic and could be used in the management of lifetime therapies of respiratory and cardiovascular disorders without any unwanted effects.